Cytokine Storm in COVID-19 in Diabetic Patients: A Review (Bangladesh Journal of Infectious Diseases, 2020)
COVID-19, a global pandemic has created a worldwide disaster since its first outbreak in December 2019 in Wuhan, China. Studies based in China have reported that people with diabetes and infected with COVID-19 showed higher hospital admission rates, serious pneumonia development, and higher mortality rates. SARS-CoV-2 can increase the metabolism of glucose by fueling immune cell overproduction - a phenomenon known as a 'cytokine storm'. Glucose metabolism is said to contribute to diverse COVID-19 outcomes. In this study, we are overviewing the linkage among SARS-CoV-2, diabetes, and cytokine storm for a better understanding of aggravating health conditions in diabetic patients due to this SARS-CoV-2 virus. In conclusion, this review will contribute to understanding complications that is rising among diabetic patients due to SARS-CoV-2 induced cytokine storm.Bangladesh Journal of Infectious Diseases, October 2020;7(suppl_2):S46-S49